Խորհրդավոր նմանակի կերպարը Էդգար Պոյի ստեղծագործության մեջ - Ա. Ր. Գալստյան (ՀՀ ԳԱԱ հրատ.)
Тема таинственного двойника присутствует в английской, немецкой, русской и американской художественной литературе романтизма. Сравнительное исследование данной темы в произведениях Эдгара По выявляет ряд особенностей в раскрытии этого образа. The theme of the mysterious counterpart is present in English, German, Russian and American literary Romanticism. The comparative study of the given subject in the works of Edgar Poe reveals a number of features in the disclosure of this image.
Keywords: Literature; Language and Literature